Observations of nonmethane organic compounds during ARCTAS - Part 1: Biomass burning emissions and plume enhancements - Hornbrook, Rebecca (author); Blake, D. (author); Diskin, G. (author); Fried, Alan (author); Fuelberg, Henry (author); Meinardi, S. (author); Mikoviny, T. (author); Richter, Dirk (author); Sachse, G. (author); Vay, S. (author); Walega, James (author); Weibring, Petter (author); et al. (Atmospheric Chemistry and Physics, 2011)
Mixing ratios of a large number of nonmethane organic compounds (NMOCs) were observed by the Trace Organic Gas Analyzer (TOGA) on board the NASA DC-8 as part of the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) field campaign. Many of these NMOCs were observed concurrently by one or both of two other NMOC measurement techniques on board the DC-8: proton-transfer-reaction mass spectrometry (PTR-MS) and whole air canister sampling (WAS). A comparison of these measurements to the data from TOGA indicates good agreement for the majority of co-measured NMOCs. The ARCTAS study, which included both spring and summer deployments, provided opportunities to sample a large number of biomass burning (BB) plumes with origins in Asia, California and central Canada, ranging from very recent emissions to plumes aged one week or more. For this analysis, BB smoke interceptions were grouped by flight, source region and, in some cases, time of day, generating 40 identified BB plumes for analysis. Normalized excess mixing ratios (NEMRs) to CO were determined for each of the 40 plumes for up to 19 different NMOCs or NMOC groups. Although the majority of observed NEMRs for individual NMOCs or NMOC groups were in agreement with previously-reported values, the observed NEMRs to CO for ethanol, a rarely quantified gas-phase trace gas, ranged from values similar to those previously reported, to up to an order of magnitude greater. Notably, though variable between plumes, observed NEMRs of individual light alkanes are highly correlated within BB emissions, independent of estimated plume ages. BB emissions of oxygenated NMOC were also found to be often well-correlated. Using the NCAR Master Mechanism chemical box model initialized with concentrations based on two observed scenarios, fresh Canadian BB and fresh Californian BB, decreases are predicted for the low molecular weight carbonyls (i.e. formaldehyde, acetaldehyde, acetone and methyl ethyl ketone, MEK) and alcohols (i.e. methanol and ...